Comprehensive comparison of MetAP2 tissue and cellular expression pattern in lean and obese rodents - Han, Jing (Diabetes Metab Syndr Obes, 2018)
BACKGROUND: Methionine aminopeptidase 2 (MetAP2) cleaves the initiator methionine from nascent peptides during translation. In both preclinical and clinical studies, the pharmacological inhibition of MetAP2 in obese subjects results in the suppression of food intake and body weight loss. However, the mechanism of action of body weight loss caused by MetAP2 inhibition remains to be elucidated, and the sites of action by pharmacological MetAP2 inhibition remain unknown. METHODS: In the present study, a comprehensive analysis of the MetAP2 expression pattern in mice was performed. RESULTS: Except for the relatively low expression in adipose tissues, MetAP2 protein was well-expressed in tissues important for metabolism, including liver, whole brain, skeletal muscle and intestine tissues. In comparison to lean mice, MetAP2 mRNA level was elevated in the intestines of diet-induced obese (DIO) mice. At the cellular level, MetAP2 exhibited a distinct high expression in central and peripheral neurons, as well as in epithelial cells lining both the small intestine and colon. In the liver of lean mice, MetAP2 protein exhibited punctate staining, which was enriched in zone three hepatocytes surrounding the central veins. In contrast, MetAP2 expression was diffuse in the liver of DIO mice. Furthermore, MetAP2 was highly expressed in immune cells that infiltrated DIO livers. CONCLUSION: Overall, these results delineate the MetAP2 expression at both tissue and cellular levels and highlight the altered MetAP2 expression under pathological conditions.